Development Strategies of Local Cuisine in Supporting the Local Community Economy on Jalan Alor, Kuala Lumpur - Julian Andriani Putri; Tuwuh Adhistyo Wijoyo; Wan Norshariza Binti Kamarulzaman; Nor Shakirah Binti Shariffudin (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
Local cuisine not only represents cultural identity but also functions as a significant economic force. This study highlights the development strategies of local cuisine on Jalan Alor, Kuala Lumpur, which has transformed into a premier culinary tourism destination. The research aims to analyze product innovation strategies, marketing, and community involvement in driving local economic growth. The research method employed is a qualitative approach with a case study design, involving in-depth interviews, participatory observation, and document studies. Findings indicate that the success of Jalan Alor is supported by sustainable culinary innovation, digital promotion strategies, quality management, and informal community support. The economic impact created includes increased vendor income, job creation, and multiplier effects on other sectors. However, challenges such as sanitation, regulation, and resilience against global crises remain major obstacles. This study recommends the need for supportive policies and training programs for culinary business operators to ensure local economic sustainability.